Design and control of DC/DC power converter used as a battery charger with maximum power extraction from photovoltaic array - Hasiba, Abdallah; Qaneer, Ahmad (My University, 2019)
Designed the DC-DC buck converter and selected the battery that we will charge. The buck converter was chosen because the battery needs a higher voltage than its voltage to be charged from the solar cell. We extracted the maximum power by using p&o algorithm, a method that tracks and monitors the point at which the power extracted from the solar panels is the maximum and maintains this value by calculating its duty cycle and entering it on the PWM to control converter switch (the MOSFET) so that it gives us on the terminals of the converter (voltage and current at maximum point) extracted From the solar panels. Furthermore, the system has been designed using MATLAB